Applicability of existing CRTS II ballastless track – Continuous girder bridge system under near-field transverse rare earthquake. (15th December 2022) - Feng, Yulin; Li, Hongyan; Yu, Jian; Jiang, Lizhong; Zhou, Wangbao; Wu, Gang
Highlights: An earthquake-induced residual deformation database for key components of the existing CRTS II ballastless track- continuous girder bridge system under near-field rare earthquakes was constructed. The characteristic curve of earthquake-induced residual deformation for track key components is developed using the hypothesis testing principle and statistical inference technique. The overlimit state analysis and applicability evaluation of the key components both of track and bridge under near-field rare earthquakes were analysed. Abstract: The earthquake-induced applicability of key components of the existing high-speed railway CRTS II ballastless track-continuous girder bridge system (HSRCCB) is not clear. The fine simulation model of the HSRCCB is developed herein. Latin hypercube sampling is used to consider the uncertainty of ground motion and HSRCCB modeling parameters. Earthquake-induced residual deformation sample database for key components of the HSRCCB under near-field rare earthquakes is constructed. Furthermore, overlimit state analysis and applicability evaluation of bridge key components are performed using the statistical inference method. The characteristic curve of earthquake-induced residual deformation for track key components is developed using the hypothesis testing principle and statistical inference method, and the overlimit state analysis and applicability evaluation are carried out accordingly. The results show that after the near-field rare earthquake, the bearing undergoes large transverse residual deformation, as well as a longitudinal residual deformation. The box girder has an obvious transverse offset; However, the transverse and longitudinal residual deformation of track key components is smaller than that of the bearing. The maximum overlimit rate of residual deformation of fixed bearing and sliding bearing is 98%, indicating that most of the bearing gets destroyed during the process. Earthquake-induced bending and shear failure do not commonly occur at the abutment/pier bottom. The longitudinal residual deformation overlimit rate of the sliding layer and friction plate is relatively large, reaching more than 82% and 47%, respectively. Shear slots, shear steel bars, and fasteners are not easy to overrun. The overlimit rate of transverse residual deformation of lateral blocks is low, CA mortar and fasteners residual deformation overlimit rate tends to be 0. The bearing is no longer applicable. The shear force and bending moment at the abutment/pier bottom, shear slots, shear steel bars, CA mortar, and fasteners applicability all meet the requirements, while the sliding layer, friction plate, and lateral blocks are difficult to meet the applicability requirements. Among them, the applicability index value of the longitudinal residual deformation of the sliding layer is as high as 181.94, indicating that the sliding layer is far from meeting the seismic design requirements of near-field rare earthquakes. Thus, attention should be paid to the seismic design.